The sum of the first four terms of the sequence is 22.
In this question,
The formula of sum of linear sequence is
![S_n =\frac{n}{2}(2a+(n-1)d)](https://tex.z-dn.net/?f=S_n%20%3D%5Cfrac%7Bn%7D%7B2%7D%282a%2B%28n-1%29d%29)
The sum of the first ten terms of a linear sequence is 145
⇒ ![S_{10} =\frac{10}{2}(2a+(10-1)d)](https://tex.z-dn.net/?f=S_%7B10%7D%20%3D%5Cfrac%7B10%7D%7B2%7D%282a%2B%2810-1%29d%29)
⇒ 145 = 5 (2a+9d)
⇒ ![\frac{145}{5} =2a+9d](https://tex.z-dn.net/?f=%5Cfrac%7B145%7D%7B5%7D%20%3D2a%2B9d)
⇒ 29 = 2a + 9d ------- (1)
The sum of the next ten term is 445, so the sum of first twenty terms is
⇒ 145 + 445
⇒ ![S_{20} =\frac{20}{2}(2a+(20-1)d)](https://tex.z-dn.net/?f=S_%7B20%7D%20%3D%5Cfrac%7B20%7D%7B2%7D%282a%2B%2820-1%29d%29)
⇒ 590 = 10 (2a + 19d)
⇒ ![\frac{590}{10}=2a+19d](https://tex.z-dn.net/?f=%5Cfrac%7B590%7D%7B10%7D%3D2a%2B19d)
⇒ 59 = 2a + 19d -------- (2)
Now subtract (2) from (1),
⇒ 30 = 10d
⇒ d = ![\frac{30}{10}](https://tex.z-dn.net/?f=%5Cfrac%7B30%7D%7B10%7D)
⇒ d = 3
Substitute d in (1), we get
⇒ 29 = 2a + 9(3)
⇒ 29 = 2a + 27
⇒ 29 - 27 = 2a
⇒ 2 = 2a
⇒ a = ![\frac{2}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B2%7D)
⇒ a = 1
Thus, sum of first four terms is
⇒ ![S_4 =\frac{4}{2}(2(1)+(4-1)(3))](https://tex.z-dn.net/?f=S_4%20%3D%5Cfrac%7B4%7D%7B2%7D%282%281%29%2B%284-1%29%283%29%29)
⇒ ![S_4 =2(2+(3)(3))](https://tex.z-dn.net/?f=S_4%20%3D2%282%2B%283%29%283%29%29)
⇒ S₄ = 2(2+9)
⇒ S₄ = 2(11)
⇒ S₄ = 22.
Hence we can conclude that the sum of the first four terms of the sequence is 22.
Learn more about sum of sequence of n terms here
brainly.com/question/20385181
#SPJ4